The transition of the agro-food system: lessons from organic farming in the Lisbon Metropolitan Area - Salavisa, I.; Ferreiro, M. F.; Bizarro, S. (Sustainability, 2021)
The paper presents a study on the transition of the agro-food system in Portugal through the analysis of case studies in the Lisbon Metropolitan Area. The theoretical framework draws on the literature on the transition of sociotechnical systems, taking into account the multidimensional nature of the food system (ecological, environmental, socioeconomic and cultural). Social and institutional innovation, technological innovation, public policy impact, and the interactions with the dominant regime are the main dimensions guiding the study of the organic farming initiatives. We identified the supportive policy measures, the role of producers’ networks, the relevance of values, and the obstacles and challenges these initiatives face in their growth process. While the results are in line with the theoretical debate, they also provide new insights on the selection environment, the networks’ dual nature and the existence of different development paths within the organic food niche. One of the main conclusions is that organic farmers perceive the regulatory framework as unfair relative to that of conventional agriculture. Therefore, it is crucial to change this framework to speed up the transition of the agro-food system in Portugal and at the European level.